Transition of sulphide self-heating from Stage A to Stage B, S. Moon, F. Rosenblum, Y.H. Tan, K.E. Waters, and J.A. Finch - S. Moon; F. Rosenblum; Y. H. Tan; K. E. Water; J. A. Finch (The Southern African Institute of Mining and Metallurgy, 2020)
Previous work has shown that sulphide self-heating occurs in three distinct stages referred to as Stage A, Stage B and Stage C. In this paper the focus is on the transition from Stage A to Stage B, which occurs at ca. 100OC. Background literature hints that the transition corresponds to the transformation of the rhombic form of elemental sulphur to the more reactive monoclinic form that occurs at 96OC. A test apparatus is modified for adiabatic heating to track the transition. The results support this transformation of sulphur as being key to the transition, and the transition temperature is thus modified to 96OC. Variations in a sample’s response under adiabatic conditions are observed and possible reasons are discussed. Testing in adiabatic mode provides new insights into the sulphide self-heating process that complement the test designed to identify propensity to self-heat. Keywords: Self-heating; Stage A/Stage B; transition; rhombic/monoclinic elemental sulphur; adiabatic heating